EDUKASI PENGGUNAAN CAMPURAN AIR LAUT DAN AIR CUCIAN BERAS PUTIH SEBAGAI SUPLEMAN HARA BAGI TANAMAN PADA SISWA SMK PERIKANAN - muktaridha, muktaridha; S, Irhami; Muliyana, Agusriati; Rahmayanti, Fitria; Febrina, Citra Dina; Hasibuan, M Barru Airil Fizra; Syahril, Alfis (Universitas Mataram, 2024)
The most abundant natural resource on earth is sea water, because most of the earth's surface is covered by oceans. This resource can be utilized by farmers to reduce pressure on increasingly limited freshwater resources. As well as the increasing need for efficient and sustainable fertilizer. Sea water is rich in nutrients such as nitrogen (N), phosphorus (P), and potassium (K), which act as essential nutrients for plant growth. Utilization of sea water can be an effective alternative to conventional fertilizer. Students can introduce seawater as fertilizer for the community from an early age. This is a good step to take because students are still open to accepting new things as innovations in the agricultural sector. Based on this, this service aims to provide information to students about the benefits of sea water as a source of complete nutrition for plants. This community service activity was carried out on August 12 2023 at SMK Negeri 1, Meureubo District, West Aceh Regency. This activity was filled with socialization and education activities on making plant nutritional supplements using seawater solutions. Apart from that, there was also a demonstration of making plant nutritional supplements using seawater solutions. Based on the activities that have been carried out, these students show very high activity and enthusiasm. This can be seen from students' positive responses to reporting new understanding obtained after the learning process was completed. Carrying out this service will also help open up new insights for students to be more creative and critical in thinking about utilizing and protecting their environment.